2008
DOI: 10.1016/j.ijid.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of multidrug-resistant tuberculosis in Georgia

Abstract: MDR-TB has emerged as a serious public health problem in Georgia and will greatly impact TB control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 11 publications
4
34
2
6
Order By: Relevance
“…The high resistance of MTB to INH and RIF-the two main drugs in TB treatment-is an alarming sign. In other studies, SM and INH have been reported as more common compared to the other first-line drugs (21,22). Other patterns of anti-TB resistance also existed.…”
Section: Discussionmentioning
confidence: 83%
“…The high resistance of MTB to INH and RIF-the two main drugs in TB treatment-is an alarming sign. In other studies, SM and INH have been reported as more common compared to the other first-line drugs (21,22). Other patterns of anti-TB resistance also existed.…”
Section: Discussionmentioning
confidence: 83%
“…Another possible explanation for the association between intravenous drug use and drug resistant TB could be related to close contacts of drug users and transmission of resistant strains within this group [25] [27]. As we do not have genotyping data available, we cannot exclude the existence of possible clusters.…”
Section: Discussionmentioning
confidence: 99%
“…While rates of HIV infection in Georgia and Belarus are low, these former Soviet Union republics have in the past reported incredibly high rates of MDR-TB among both new (10.5% in Georgia and 35.5% in Belarus) and previously treated TB patients (53.1% Georgia and in 76.5% in Belarus). 16,17 These programs also share common features in their introduction of BDQ in their settings. Four of the five countries began using BDQ as part of compassionate use/expanded access programs, and a positive experience with the drug under these conditions led to the decision to scale up access to the drug more widely.…”
Section: Discussionmentioning
confidence: 99%